6-(3x-4)=-x-6

Simple and best practice solution for 6-(3x-4)=-x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(3x-4)=-x-6 equation:


Simplifying
6 + -1(3x + -4) = -1x + -6

Reorder the terms:
6 + -1(-4 + 3x) = -1x + -6
6 + (-4 * -1 + 3x * -1) = -1x + -6
6 + (4 + -3x) = -1x + -6

Combine like terms: 6 + 4 = 10
10 + -3x = -1x + -6

Reorder the terms:
10 + -3x = -6 + -1x

Solving
10 + -3x = -6 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
10 + -3x + x = -6 + -1x + x

Combine like terms: -3x + x = -2x
10 + -2x = -6 + -1x + x

Combine like terms: -1x + x = 0
10 + -2x = -6 + 0
10 + -2x = -6

Add '-10' to each side of the equation.
10 + -10 + -2x = -6 + -10

Combine like terms: 10 + -10 = 0
0 + -2x = -6 + -10
-2x = -6 + -10

Combine like terms: -6 + -10 = -16
-2x = -16

Divide each side by '-2'.
x = 8

Simplifying
x = 8

See similar equations:

| 108-3x=3x | | 6+2x=3+x | | 6x-5=6x | | .7x-2=.5 | | -2=5+a/2 | | 2x+18=93 | | y-5=-(5-7) | | 3k-2m+4=0 | | -8x+14=-2*4x-7 | | 3+3x=5(x+5) | | -8=x/4+6 | | (x-7)=2 | | 512/16 | | y=-3/4x^2 | | 2z+4=5z+2-2z | | X=4X^4-12X^2+6 | | SolveX=4X^4-12X^2+6 | | -6y+3y+4=-3y+4 | | .3x+1.24=2.14 | | 98-3x=15x+16 | | 18*3x=11 | | 2x=4(5-6) | | 8-9x=116-37x | | 2x^3=2 | | 0.3x+1.8=0.4(x+5)+2 | | .3x+.5=-.1 | | 5+(2x-3)=16 | | 54/x=9 | | 4+12x=36 | | 52x+8y-13x-19y= | | -7(7m-6)-2(-8m+4)=-65 | | 94.2*3.14=15r |

Equations solver categories